Diagnostic Value of Plasma Pentraxin3- Level For Diagnosis of Erectile Dysfunction - Eren, Ali Erhan; Ersay, Ahmet Re?it; Demirci, Emrah; Alan, Cabir; Basturk, Gökhan (Urology Journal, 2018)
Purpose: Erectile dysfunction (ED) is a sexual dysfunction described as the inability to develop or maintain an erection of the penis adequate for sexual intercourse, and its prevalence increases with age. Seen as a common sexual disorder worldwide, organic causes are the underlying reason for 80 percent of ED cases, with the most characteristic pathology responsible for organic ED being atherosclerosis. This study investigates the diagnostic value of plasma PTX-3 levels in arterial ED. Materials and Methods: This study included a total of 45 patients who were admitted to the urology and cardiology outpatient clinics of the Medical Faculty of Canakkale Onsekiz Mart University (COMU) and consented to participate in this study. Patients were categorized into three equal groups in number: (1) patients with ED diagnosed with coronary artery disease (CAD) (15 patients in total); (2) patients with ED not having coronary artery disease or any other equivalent diseases (diabetes mellitus, hypertension and hyperlipidemia) (15 patients in total); and (3) ordinary patients with no ED (15 patients in total). An interview was conducted at the andrology polyclinic with each patient in order to ascertain detailed information on their medical and sexual history and on demographic characteristics. All patients were also administered the International Index of Erectile Function (IIEF) questionnaire. Result: The findings from this study investigating the diagnostic value of plasma PTX-3 levels in ED were statistically significant for two comparisons: the differences between the peripheral blood and cavernous blood values of the patient groups (group 1 and 2) and the control group (group 3), and the differences between the peripheral blood and cavernous blood values of group 2 (patients with ED who do not have CAD) and the control group (group 3). Conclusion: As PTX-3 is more specific than the formerly recognized biochemical markers in endothelial dysfunction, it can be used in the diagnosis of vascular originated ED.